Strengthening the Digital Branding of Cireng Senja MSME Through Visual Identity Development and Social Media Activation - Rachmi Satwhikawara; Carla Roselani Haryadi; Ferawati Natalita (International Journal Of Community Service, 2026)
Cireng Senja is a small asal micro, small, and medium enterprise (MSME) culinary in Jatireja, East Cikarang that sells affordable cireng through self service or prasmanan concept. Despite average production of around 250 pieces reported by the partner per day, growth of their business was limited as there was no adequate visual identity and consistent digital product details or an online channel to market the products. Objective: To conduct a community engagement program using low cost digital branding intervention to bolster the marketing readiness status of the partner. Using the participatory action learning method of initial observation, partner consultation, co-designing branding assets, activating on social media and output-based evaluation, the programme was conducted between 12 November and 18 December 2025. The program also generated an official logo, a digital menu, promotional materials and an Instagram account (@cirengsenjaku). From an offline-only business with no formal wordmark to a business ready with consistent visual identity and shareable digital marketing assets (before & after assessment) Total realized budget of IDR 20,000 for the intervention as this had moved from physical packaging reoccuring cost into evergreen digital assets. The assessment only took output fulfillment and readiness for operations into account; sales growth after the program was not counted. This program highlights that a combination of skill transfer and simple digital supports can help assist micro food businesses to brand without significant financial investment. Keywords: Digital branding, Food business, MSME, Community engagement and Social media marketing.